Perfect match - Picoult, Jodi, 1966- (New York : Washington Square Press, 2002)
District Attorney Nina Frost and her husband, Caleb, face a nightmare when they discover that their young son Nathaniel has been molested, a trauma that has left him mute, terrified, and unable to reveal the identity of his attacker.
Includes Readers Club guide.
Keywords: Sexually abused children -- Fiction; Public prosecutors -- Fiction; Mothers and sons -- Fiction; Women murderers -- Fiction; Married women -- Fiction; Women lawyers -- Fiction; Revenge -- Fiction; Maine -- Fiction; Domestic fiction; Legal stories